Pengaruh Komitmen Organisasi dan Kepuasan Kerja terhadap Turnover Intention pada Karyawan Bagian Pemetikan PT. XYZ - Angraini, Siti Aulia; Khaerul Rizal Abdurahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of organizational commitment and job satisfaction on turnover intention of employees in the picking department of PT. XYZ. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 35 respondents who have worked for more than one year. Data were analyzed using multiple linear regression with the help of the SPSS version 25 program, as well as through a series of validity, reliability, and classical assumption tests. The results of the study indicate that both organizational commitment and job satisfaction partially and simultaneously have a negative and significant effect on turnover intention. The conclusion of this study shows that the higher the organizational commitment and job satisfaction of employees, the lower the level of employee desire to leave the company. Keywords: Organizational Commitment, Job Satisfaction, Turnover Intention